EVIDENCE OF EARLY PALAEOZOIC CONTINENTAL RIFTING FROM MAFIC METAVOLCANICS OF SOUTHERN PELORITANI MOUNTAINS (NORTH-EASTERN SICILY, ITALY) - Cirrincione, Rosolino; Fiannacca, Patrizia; Lo Giudice, Antonino; Pezzino, Antonino (Ofioliti, 2005)
Pre-Hercynian magmatic rocks are widespread in the Palaeozoic basement of the Peloritani Mountain Belt. The metabasites of the Mongiuffi-Melia area (SE Peloritani) represent the largest magmatic products of Early Palaeozoic. These rocks occur as mafic lava flows and metavolcanoclastites often preserving relict igneous textures. They were weakly metamorphosed during the Hercynian orogenesis and show sub-greenschist metamorphic assemblages overprinting the original igneous parageneses. The geochemical features of these rocks indicate an alkali basaltic composition and a within-plate to P-MORB affinity. Basaltic protoliths of metabasites were produced by partial melting of variably enriched mantle sources and experienced fractionation and little crustal contamination during their ascent. Overall data are consistent with a geodynamic environment related to an early stage of tectonically dominated continental rifting. These metabasites represent the only evidences of a Cambro-Ordovician extensional event in the Peloritani domain of the former Alboran microplate. Their features are consistent with a possible location of this terrane at the south-western termination of the South Armorican Ocean during the Early Palaeozoic.